The Role of Business Incubators in Fostering Innovation and Technological Advancement in India - Dikshit, Sukanya; Homavazir, Zuleika; Gambhir, Vinima; Homavazir, Malcolm (AMC Indian Journal of Entrepreneurship, 2023)
Purpose : This study examined how Indian business incubators foster innovation and technological growth. Given India’s growing economy and burgeoning startup scene, it is imperative to comprehend the role of business incubators. Methodology : A thorough literature research and case study analysis were used to determine the effect of business incubators. The study assessed their contributions to financial access, mentorship, collaboration facilitation, and innovation support. Findings : As essential components of India’s entrepreneurial ecosystem, business incubators have been shown to be effective in fostering innovation and directing the expansion of start-ups. Their contributions to fostering partnerships, guaranteeing mentorship, and streamlining financing availability stood out as noteworthy highlights. However, a number of issues that these incubators encountered also surfaced. Practical Implications : Acknowledging and enhancing the advantages of business incubators may help to establish India as a center for innovation. Resolving these issues might result in a start-up environment that is more influential and long-lasting. The results opened the door for stakeholders and policymakers to increase the efficacy of the incubation model. Originality : While numerous studies discussed the start-up ecosystem in India, this work offered a comprehensive understanding of business incubators’ instrumental role in fostering innovation and technology advancement.